2002
DOI: 10.1152/ajpheart.00593.2002
|View full text |Cite
|
Sign up to set email alerts
|

Vascular adaptations to pregnancy in mice: effects on myogenic tone

Abstract: The mechanisms underlying vascular adaptations in pregnancy remain to be fully elucidated. One of the contributory mechanisms for reduced vascular tone may be a reduction of myogenic tone. Myogenic tone was assessed as the difference between internal diameter in the presence and absence of external calcium at different intramural pressure steps (60–100 mmHg). Myogenic responses were reduced in resistance-sized mesenteric and main uterine arteries in late pregnant compared with nonpregnant C57BL/6J mice. In ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 40 publications
4
61
1
Order By: Relevance
“…Previous studies (16,38,39,51) have shown a decrease in pressure-induced myogenic tone of uterine, mesenteric, and renal arteries in pregnant mice and rats. In contrast, myogenic reactivity of myoendometrial radial uterine arteries was found to be increased in pregnant rats (41).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies (16,38,39,51) have shown a decrease in pressure-induced myogenic tone of uterine, mesenteric, and renal arteries in pregnant mice and rats. In contrast, myogenic reactivity of myoendometrial radial uterine arteries was found to be increased in pregnant rats (41).…”
Section: Discussionmentioning
confidence: 91%
“…Myogenic response has been found as either increased or decreased in uterine arteries of pregnant, compared with nonpregnant, rats, mice, and rabbits (5,42,51).…”
mentioning
confidence: 99%
“…Additionally, reduced activity of endothelial NOS and, perhaps, nitric oxide bioavailability along with impaired vascular function in offspring from DR dams has been demonstrated [5,41]. Our previous studies showed that endothelial removal from uterine arteries of pregnant mice resulted in a comparable increase in myogenic responses to that found by NOS inhibition [42]. Therefore, we speculate that impaired endothelial function causes a relative deficiency of nitric oxide-mediated vasodilation during pregnancy and manifests as increased myogenic reactivity in the offspring of DR rat dams.…”
Section: Fig 2 Myogenic Responses In Radial Uterine (A) and Mesentementioning
confidence: 94%
“…On day 20 of pregnancy (term ϭ 22 d) dams were killed under surgical plane anesthesia (intraperitoneal injection of sodium pentobarbital, [Somnotol, MTC Pharmaceuticals, Ontario, Canada, 42.25 mg/kg body weight]), the abdominal cavity was opened, and the fetuses were rapidly delivered by caesarean section and placed in cold Dulbecco's medium. Dulbecco's medium contained Dulbecco's Modified Eagle medium base (Sigma Chemical Co.), supplemented with 1 mmol/L sodium pyruvate, 25 mmol/L sodium bicarbonate, 5 mmol/L HEPES, 5 mmol/L glucose, and nutrient amino acids and vitamins that improved viability of vessels studied in vitro (21).…”
Section: Methodsmentioning
confidence: 99%